4 - Insertion Socioprofessionnelle des Jeunes au Bénin : entre Employabilité Publique, Privée ou Personnelle - Gilbert Coovi; Coffi Rémy Noumon (African Sociological Review, 2020)
Thetransition from school to working life is an increasingly long, precarious and sometimes lif e long journey. The providential state, automatic provider of employment at the end of f ormal education no longer exists. The youth unemployment rate is increasing overtime. The millennium development goals (MDGs) of eradicating poverty, guaranteeing prosperity for all, are being mortgaged. Young Beninese are not exception to the situation of an ever-increasing rate of unemployment. Theobjective of the research is to analyze the factors thataffect socio- professional insertion capacity of youth in Benin. Theapproach is qualitative, inspired by the strategic analysis of M. Crozier (2018), G. S Becker’s theory of human capital (1965), and that of transition to the youth employment market of S. Elder. and K. S Koné (2014) The sampling technique is that of reasoned choice used for two target groups namely, public service agents f or employment and recruitment prof essionals. The way survey is used to interview young people who have or have not successfully completed their socio-occupational insertion. Theliterature revue, the semi-directive interview are conducted from the related tools. A total of 27 social actors are interviewed with specific interview guides administered to each target group. Outcomes show that internal and external factors affecting youth unemployment are, institutional barriers, university-industry linkage, lack of resources and creativity for self- employment, lack of courage among young people to embark on the entrepreneurial adventure. These outcomes challenge both the youth themselves f or lack of creativity as well as that governments and education experts foradaptation of training programs to the needs of the labor market.